2014
DOI: 10.1021/ie501474t
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Two-Phase Flow Structure in a Modified Gas–Solid Fluidized Bed

Abstract: Transient signals were registered in a modified fluidized bed and statistically analyzed. Particle agglomerates in the emulsion were identified from signals and the agglomerate properties were investigated. The volume fraction of the bubble phase varied from 0.16 to 0.52 with operation pattern and spatial positions. Mean solid holdup and its standard deviation inside bubbles significantly increased when operation pattern transitioned from bubbling fluidization to turbulent fluidization, while the increasing te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The leaner part involves the dispersed and suspended particles, bubble noses, and bubble wakes, while the denser part is the particle agglomerate. Furthermore, based on the general guidelines from Soong et al for identification of particle clusters in dilute gas–solid flow, a criterion was proposed for identification of particle agglomerates in a dense phase fluidized bed: The solid holdup in particle agglomerates must be above the time-averaged solid holdup at the minimum fluidization. The perturbation in the solid holdup, due to occurrence of agglomerate, must be greater than the random fluctuations in the solid holdup of the emulsion. The solid holdup increase must be sensed for a sampling volume with a characteristic length scale smaller than the anticipated agglomerate dimension but orders of magnitude greater than the individual particle dimension. …”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaner part involves the dispersed and suspended particles, bubble noses, and bubble wakes, while the denser part is the particle agglomerate. Furthermore, based on the general guidelines from Soong et al for identification of particle clusters in dilute gas–solid flow, a criterion was proposed for identification of particle agglomerates in a dense phase fluidized bed: The solid holdup in particle agglomerates must be above the time-averaged solid holdup at the minimum fluidization. The perturbation in the solid holdup, due to occurrence of agglomerate, must be greater than the random fluctuations in the solid holdup of the emulsion. The solid holdup increase must be sensed for a sampling volume with a characteristic length scale smaller than the anticipated agglomerate dimension but orders of magnitude greater than the individual particle dimension. …”
Section: Analysis Methodsmentioning
confidence: 99%
“…Sun et al 5 introduced continuous wavelet transform technique to analyze the particle vortex behavior and the results show that the timescale of a particle vortex has a linear relationship with the wavelet scale. Liu et al 6 found that solid holdup of the emulsion phase varies over a wide range, from 0.49 to 0.73. They proposed that the emulsion phase can be divided into two parts: a leaner part and a denser part.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows a typical time series of solid holdups. On the basis of the identification of the particle agglomerate proposed by Liu, a denser part of solid holdup greater than the time-average solid holdup at the minimum fluidization, ε s,mf , is assumed to be particle agglomerate. Then, the agglomerate peaks in two channels can be matched if the correlation coefficient ρ XY is >0.9. The hydrodynamics properties of agglomerates, such as the diameter, frequency, and solid holdup, are then calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It acts in a radial direction and has magnitude in which ν is Poisson’s ratio. For many materials, Poisson’s ratio can be taken to be equal to 0.25. q 0 is the value of maximum pressure at the center of the surface of contact, which gives as For two agglomerates in contact, the radius, a , of the surface of contact and the displacement, α, (shown in Figure ) are given as in which Because the solid holdup of agglomerates varies slightly, the two colliding agglomerates are assumed to have the same elastic properties. Substituting eqs , , and into eq gives Figure shows the schematic of an agglomerate consisting of several particles.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…As summarized in our previous studies [12,13] , the design idea of the ACC was originated from a recirculation fluidized bed (RCFB) [14,15] . For RCFBs, many studies have been conducted to obtain the profiles of bed density and solids velocity [16,17] , particle residence time distribution [18] , particle circulating velocity [19,20] , and cold and hot particle mixing degree [21,22] in the critical regions. However, an ACC bears significant differences to a RCFB in terms of the double distributor design and system configuration.…”
Section: Introductionmentioning
confidence: 99%